The Evolution of Islamic Economic Thought and Its Implications for Sharia Accounting: A Review of the Literature - Raehal, Adit Rahmat; Kuswantoro, Dedi; Kholmi, Masiyah (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2025)
This study examines the evolution of Islamic economic thought from classical to contemporary periods and its influence on the development of sharia accounting. Focusing on principles of justice, transparency, and accountability, the study explores how sharia values shape an accounting system that supports a fair and sustainable economy. Using a literature study approach, it integrates classical sources such as the Qur'an and Hadith with accredited journals and recent research. The results show that sharia accounting functions not only as a recording tool but also as an instrument to realize maqashid sharia in the global economic context.